The well-being of Russian cities: does location matter? - Vera Ivanova (European Regional Science Association (ERSA), 2015)
Using the data covering the time period from 1996 till 2011, I estimate a spatial autoregressive model of wages' growth rates across Russian cities. I find that wages in Russian cities exhibit convergence. I also test whether city population (which is a proxy for city size) has positive impact on the speed of convergence. Using geographical location characteristics (longitude, latitude, average annual temperature, soil quality) and historical data (the first two censuses of the country) as instruments for population, I find a positive relationship between city size and city growth. In other words, cities converge in wages, but diverge in size.
Keywords: R12; O18; 330; cities; wages; convergence; spatial econometrics